2022
DOI: 10.3389/fonc.2022.878546
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry and Bioinformatics Identify GPX8 as a Potential Prognostic Biomarker and Target in Human Gastric Cancer

Abstract: BackgroundGlutathione peroxidase 8 (GPX8) is a type II transmembrane protein with rare structural features belonging to the glutathione peroxidase family. The function of GPX8 in stomach adenocarcinoma has not been discovered clearly.MethodsIn this study, we comprehensively analyzed the expression of GPX8 in stomach adenocarcinoma and discovered that it is a potential target in the treatment of stomach adenocarcinoma. The immunohistochemical staining of GPX8 and survival analysis were performed in carcinoma ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…GPX8 is a localized ER transmembrane protein that regulates ROS production and clearance in organisms [19]. Recent studies have shown that GPX8 is associated with poor prognosis in various cancers, including gastric cancer, lung cancer, and glioma [23,25,48]. In clear cell renal cell carcinoma, GPX8 regulates NNMT expression through the IL6-STAT3 signaling axis and inhibits ccRCC cell survival by blocking this axis through activation of AMPK [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPX8 is a localized ER transmembrane protein that regulates ROS production and clearance in organisms [19]. Recent studies have shown that GPX8 is associated with poor prognosis in various cancers, including gastric cancer, lung cancer, and glioma [23,25,48]. In clear cell renal cell carcinoma, GPX8 regulates NNMT expression through the IL6-STAT3 signaling axis and inhibits ccRCC cell survival by blocking this axis through activation of AMPK [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that GPX8 can maintain the invasive mesenchymal-like phenotype of breast cancer cells through the IL-6/STAT3 axis [23]. GPX8 has been recognized as a prognostic marker for cancers such as gastric cancer and primary glioma [24,25]. In clear cell renal cell carcinoma, GPX8 silencing inhibits tumorigenesis by regulating nicotinamide N-methyltransferase (NNMT) [26].…”
Section: Introductionmentioning
confidence: 99%
“…GPX8 could promote the growth of gastric cancer cells via activation of the Wnt signaling pathway [39]. Several studies have reported the GPX8 is a potential prognostic marker in GC [40,41]. Abnormal methylaion status of SMPD3 was associated with clinical characteristics in renal cell cancer [42].…”
Section: Discussionmentioning
confidence: 99%